MOLECULAR CHARACTERIZATION OF TRICHODERMA SPP. AGAINST COLLETOTRICHUM GLOEOSPORIOIDES PENZ. WITH RAPD AND ITS-PCR - ANU A. MATHEWS,; BASHA, S. THAHIR; REDDY , N. P. ESWARA (The Bioscan, 2023)
Genetic variability among the isolates of Trichoderma spp. against Colletotrichum gloeosporioides (Penz.) Penz. and Sacc. was studied using molecular techniques like RAPD and ITS-PCR. The RAPD banding pattern reflected the genetic diversity among the isolates with the formation of three clusters. ITS region of rDNA amplification with genus specific ITS1 and ITS4 universal primers produced products that varied in size from 566 to 657 bp in all the isolates. These results indicated polymorphism at ITS region of rDNA among the isolates of Trichoderma.